ENHANCE INDUSTRIAL COMPETITIVENESS THROUGH IMPROVED YLANG ESSENTIAL OIL QUALITY AND SYNERGY AMONG MEMBERS OF THE CLUSTER - Dyah Erni Widyastuti; Sukardi Sukardi; Vina Salviana DS; Rahmad Dwi S; Tutik Sulistyowati (UNEJ e-Proceeding, 2012)
Indonesia is one of the ten States exporters of essential oils. Some of the problems faced by the production centers since the post-harvest crop up because of yet to implement Good Agricultural Practices (GAP). In the refining process, still not familiar with Good Manufacturing Practice (GMP). Marketing chain is too long and limited market access. Therefore it is necessary increase the competitiveness of industry, ylang essential oils. Research objectives are (1) Increasing the synergy between the cluster members to improve ylang essential oil industry towards national and international scale. (2) Increasing productivity and supply continuity of raw materials as well as ylang flower essential oils product quality improvement, (3) Expanding market product access accurately. Activity location is in Blitar East Java Province, as one of the essential oils industrial centers in Eastern Indonesia. Putri Kencana (Program Produk Unggulan Industri Kecamatan) is an area of potential improvement programs implemented through industrial clusters such as clusters of palm-based Manggar Sari; industrial-based Essential Java patchouli, clove, ylang, ginger, and clusters of food-based industries Sari Raos. The approach used in this research is the empowerment of communities through participatory integrative model that is empowerment by involving the community in a comprehensive manner, from the upstream to downstream. The results showed that (1) As a system of agribusiness development ylang essential oils, found a variety of issues from upstream to downstream,such as production efficiency. (2) There is positive potential that can be developed as a tough businessman, (3) Necessarily needs an agribusiness institutional ylang essential oils to enhance competitiveness, especially in the Essential Java cluster. Some issues still need to be solved simultaneously, among others they were (a) relating to the production process aspects that is the technology to improve fractionation process that will also improve the quality of ylang essential oils. (b) on the marketing aspects, the needs to strengthen the competitiveness and development of downstream industries. (c) and on the institutional aspect, the public policies is necessary to support the regulations strengthening in thebusiness chain ylang essential oils. (d) on aspects of the formation of national character, it is also needs to be strengthen and human resource assistance to establish the character of entrepreneurial and competitiveness.